Poly-ferric sulphate as superior coagulant: A review on preparation methods and properties - Nurul Aqilah Mohamad, Nurul Aqilah Mohamad; Sofiah Hamzah, Sofiah Hamzah; Nur Hanis Hayati Hairom, Nur Hanis Hayati Hairom; Mohd Salleh Amri Zahid, Mohd Salleh Amri Zahid; Khairol Annuar Mohd Ali, Khairol Annuar Mohd Ali; Che Mohd Ruzaidi Ghazali, Che Mohd Ruzaidi Ghazali; Andrei Victor Sandu, Andrei Victor Sandu; Mohd Mustafa al Bakri Abdullah, Mohd Mustafa al Bakri Abdullah; Petrica Vizureanu, Petrica Vizureanu (De Gruyter, 2023)
Iron-based coagulants are widely used in wastewater treatment due to their high positively charged ion that effectively destabilise colloidal suspension, and thus contribute to the formation of insoluble flocs. Ferric chloride, ferrous sulphate, and poly-ferric sulphate (PFS) are examples of iron-based coagulants that are highly available, and are beneficial in producing denser flocs, thereby improving settling characteristics. This work aims to review the preparation methods of PFS and critically discuss the influence of these methods on the PFS properties and performance as a chemical coagulant for water and wastewater treatment. In polymeric form, PFS is one of the pre-hydrolysing metallic salts with the chemical formula [Fe2(OH)n(SO4)3−n/2]m (where, n < 2, m > 10) and has a dark brownish red colour as well as is more viscous and less corrosive. PFS has an amorphous structure with small traces of crystallinity, containing both hydroxyl and sulphate functional groups. It has been applied in many industries including water or wastewater treatment which is also discussed in this study. It has the ability to remove pollutants contained in water or wastewater, such as turbidity, colour, chemical and biological oxygen demand, phosphorus, and others. This study also provides a review on the combination of PFS with other chemical coagulants or flocculants in the coagulation/flocculation process, and also flocs formed after a more stable treatment process.